2019
DOI: 10.1177/0898756419873986
|View full text |Cite
|
Sign up to set email alerts
|

Two Randomized Trials Demonstrate Lactic Acid Supplementation in Pet Food Inhibits Dental Plaque, Calculus, and Tooth Stain in Cats

Abstract: Background: Dental concerns are some of the most common health problems affecting companion animals. A variety of foods, treats, and chews comprising different mechanical and chemical technologies have been investigated as a means of promoting oral health. Here, we investigate the chemical technology, lactic acid added to a commercially available food, for its ability to inhibit dental plaque, calculus, and tooth stain accumulation in cats. Methods: Two separate feeding trials assessed the utility of a nutriti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…The procedures used in this study demonstrated low intra-and inter-grader variability, and the computer derived coverage calculations correlated well to a human grader. The quantification of oral substrate accumulation using QLF derived images was able to demonstrate the ability of established dental diets 23,43 to inhibit oral substrate accumulation. This study differs from previous studies in a number of ways.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The procedures used in this study demonstrated low intra-and inter-grader variability, and the computer derived coverage calculations correlated well to a human grader. The quantification of oral substrate accumulation using QLF derived images was able to demonstrate the ability of established dental diets 23,43 to inhibit oral substrate accumulation. This study differs from previous studies in a number of ways.…”
Section: Discussionmentioning
confidence: 99%
“…One group received a commercial brand cat food that was not expected to have dental biofilm prevention activity e (control); 2 groups received the same commercially available cat food supplemented with lactic acid f that has recently demonstrated the ability to reduce oral substrate accumulation (Group 1 or Group 2). 43 Fifteen cats were assigned to each group. At baseline (day 0) and at months 1, 2, and 3, teeth from each cat were imaged using the QLF system while under anesthesia.…”
Section: Feline Studymentioning
confidence: 99%
“…There is a multitude of literature devoted to these topics, but they fell into several categories that are worth mentioning briefly. A bulk of the literature is associated with common household pets such as dogs ( Carroll et al, 2020 ; Clarke et al, 2011 ; Quest, 2013 ) and cats ( Bellows et al, 2012 ; Scherl et al, 2019 ) and the effort to combat plaque buildup through treats and chew toy interventions. Other common wild and domesticated animals that have been studied for oral pathologies and calculus deposition include horses ( Earley and Rawlinson, 2013 ), camels ( Eze et al, 2012 ), pandas ( Jin et al, 2012 ), brown bears ( Wenker et al, 1998 ), dolphins ( Loch et al, 2011 ) and captive big cats ( Kapoor et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%